2019
DOI: 10.21037/jtd.2019.06.35
|View full text |Cite
|
Sign up to set email alerts
|

House dust mite subcutaneous immunotherapy in Chinese patients with allergic asthma and rhinitis

Abstract: The efficacy of allergen immunotherapy (AIT) has been reported with different allergens including house dust mites (HDM). HDM are the most prevalent allergens in patients with asthma and/or rhinitis in China. In addition to improving symptoms, reducing medication need, and improving quality of life, AIT can change the course of allergic disease and induce allergen-specific immune tolerance. To date, the use of AIT is becoming more acceptable in China, and there are many studies about the current clinical pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Randomize, prospektif, tek ve çift kör plasebo kontrollü çalışmalar alerjik rinitte konvansiyonel immünoterapinin etkinliğini göstermiştir (15). İmmünoterapi alerjen ekstresinin düşük dozdan başlanarak artan dozlarda, belirli aralıklarla hastaya verilmesi ve alerjenin tolere edilmesinin sağlanması esasına dayanmaktadır (16,17). Dolayısıyla AİT gündeme geldiği zaman kişinin AR, astım ve konjunktivitinin aslında tek bir hastalığın farklı parçaları olarak kabul edilmesi uygun olacaktır (18).…”
Section: Discussionunclassified
“…Randomize, prospektif, tek ve çift kör plasebo kontrollü çalışmalar alerjik rinitte konvansiyonel immünoterapinin etkinliğini göstermiştir (15). İmmünoterapi alerjen ekstresinin düşük dozdan başlanarak artan dozlarda, belirli aralıklarla hastaya verilmesi ve alerjenin tolere edilmesinin sağlanması esasına dayanmaktadır (16,17). Dolayısıyla AİT gündeme geldiği zaman kişinin AR, astım ve konjunktivitinin aslında tek bir hastalığın farklı parçaları olarak kabul edilmesi uygun olacaktır (18).…”
Section: Discussionunclassified
“…In addition, with economic development, acceleration of industrialization, and lifestyle changes in China, the morbidity rate of AR has increased. It has been reported that approximately 30 million patients are diagnosed with AR in China every year [ 3 , 4 ]. Therefore, AR has triggered significant public health problems worldwide.…”
Section: Introductionmentioning
confidence: 99%